Kinetics of Austenite Formation in a Medium-Carbon, Low-Alloy Steel with an Initial Martensite Microstructure: Influence of Prior Austenite Grain Size - Navneeth Rajakrishnan; Morteza Sadeghifar; Pinaki Bhattacharjee; Henri Champliaud; Mohammad Jahazi (Journal of Manufacturing and Materials Processing)
The impact of prior austenite grain size (PAGS) on the kinetics of austenite formation with an initial martensite microstructure was investigated in a medium-carbon, low-alloy steel. Two distinct PAGS of 117 and 330 μm, representing the range of grain sizes encountered in industries, were considered. In this analysis, high-resolution dilatometry was used to study the formation of austenite during continuous heating experiments. The analysis of the dilatometry results revealed that grain refinement accelerated the rate of austenite formation without impacting its austenite formation temperature. Intermittent quenching tests were conducted to elucidate the nucleation and growth mechanisms of austenite formation using a combination of optical, scanning electron microscopy (SEM), and electron backscatter diffraction (EBSD). The differences in austenite formation kinetics as a function of prior austenite grain size were quantified and modeled in the framework of diffusion-controlled nucleation and growth theories using the genetic algorithm optimization.